PENGARUH STRATEGI NAFKAH TERHADAP DINAMIKA KEMISKINAN DI WILAYAH HULU DAN HILIR SUNGAI CIMANUK, JAWA BARAT - Kabbaro, Hurriyatun; Hartoyo, Hartoyo; Yuliati, Lilik Noor (Jurnal Ilmu Keluarga dan Konsumen, 2016)
This study examined the effect of livelihood strategy on poverty dynamics in upstream and downstream region of Cimanuk Watershed, West Java. Study used cross-sectional and historical design. Study was conducted in Garut Disctict as upstream region and Indramayu District as downstream region. This research involved 138 families who have preschool and school child. The families were chosen by purposive sampling and the data was obtained by interview using questionnaire. Multinomial logistic regression was used to find factors influencing poverty dynamics status. The result showed that poverty in upstream region was dominated by moving into poverty dynamic, whereas poverty in downstream region was dominated by always poor dynamic. Families in downstream region have higher possibility to moving out of poverty than families in upstream region. Multinomial regression analysis showed that livelihood strategy had influence on poverty dynamics. Human capital investment in formal education and strengthening local-based livelihood patterns should be encouraged to reduce poverty.